2020
DOI: 10.1177/1391561420940838
|View full text |Cite
|
Sign up to set email alerts
|

Causal Nexus Between FDI Inflows and Its Determinants in SAARC Countries

Abstract: This article aims to understand the drivers of foreign direct investment (FDI) inflows and its nexus with its determinants such as economic growth, inflation rate, labour productivity, infrastructure development, market size, openness of the economy, political stability and corporate tax for South Asian Association for Regional Corporation (SAARC) countries. The article is based on secondary data from the World Bank and International Labour Organization (ILO) for 19 years from 2001 to 2018 for 6 SAARC countrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The study also reveals that inflation and trade openness do not impact FDI inflows for both countries. In another study, Rai and Sharma (2020) confirmed the causal associations of FDI inflows with economic size, trade flexibility and political condition in the SAARC zone. The study argues that expanding markets, trade liberalisation policies and political stability are decisive factors in attracting FDI to the region.…”
Section: Literature Review 31 Determinants Of Fdimentioning
confidence: 60%
“…The study also reveals that inflation and trade openness do not impact FDI inflows for both countries. In another study, Rai and Sharma (2020) confirmed the causal associations of FDI inflows with economic size, trade flexibility and political condition in the SAARC zone. The study argues that expanding markets, trade liberalisation policies and political stability are decisive factors in attracting FDI to the region.…”
Section: Literature Review 31 Determinants Of Fdimentioning
confidence: 60%
“…However, the study also finds that none of the tax incentives were effective in increasing gross fixed capital formation. Furthermore, Rai and Sharma (2020) examine the determinants of FDI inflows for six SAARC countries (i.e., Bangladesh, Bhutan, India, Pakistan, Nepal and Sri Lanka) using panel data. They find that CIT is one of the significant determinants of FDI inflows and the coefficient is significant and negative.…”
Section: Cit and Investmentmentioning
confidence: 99%
“…Over the last decade, China has become the largest recipient of FDI whilst simultaneously increasing its outward FDI dramatically. Rai and Sharma (2020) found that there exists a long-run, short-run and joint causal relationship between infrastructure development, market size, the openness of the economy, political stability and corporate tax and FDI inflows. Among these variables, the corporate tax is the most important one because it shows bidirectional causality with FDI inflows in the long run as well as short-run along with joint strong causality (Rai, Sharma 2020).…”
Section: Globalisation Frontiers and Enablersmentioning
confidence: 99%
“…Rai and Sharma (2020) found that there exists a long-run, short-run and joint causal relationship between infrastructure development, market size, the openness of the economy, political stability and corporate tax and FDI inflows. Among these variables, the corporate tax is the most important one because it shows bidirectional causality with FDI inflows in the long run as well as short-run along with joint strong causality (Rai, Sharma 2020). Although FDI is known to be the most stable type of international capital flow, it may be particularly susceptible to heightened uncertainty because of its high fixed costs (Choi, Furceri, Yoon 2020).…”
Section: Globalisation Frontiers and Enablersmentioning
confidence: 99%
See 1 more Smart Citation